2012
DOI: 10.1345/aph.1q689
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use and Associated Risk of Falling in a Geriatric Outpatient Population

Abstract: The addition of medications is associated with a significant increase in risk of falls in elderly patients, regardless of drug class. Further studies are needed to assess the possible increased risk of falls with increasing number of medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 13 publications
3
63
2
5
Order By: Relevance
“…Each year, about one-third of individuals over the age of 65 years living in the community will experience a fall, 5,6 and about half of these will have a subsequent fall in the following year. 6,7 Fall-related complications such as fracture, death, admission to hospital, admission to an institution, and disability increase with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, about one-third of individuals over the age of 65 years living in the community will experience a fall, 5,6 and about half of these will have a subsequent fall in the following year. 6,7 Fall-related complications such as fracture, death, admission to hospital, admission to an institution, and disability increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…5 A PIM is defined as a medication for which the potential risk for ADEs outweighs the possible clinical benefit for the patient. 11,12 The well-known Beers criteria define PIMs with the potential to increase fall risk in elderly individuals, and it is recommended that certain medication classes be avoided for elderly patients with a history of falls (unless safer alternatives are not available).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Outpatients would experience a 14% increase in fall risk with the addition of each medication beyond a four-medication regimen (OR 1.14, 95% CI 1.02-1.27; P=0.027). 35 Mizukami et al examined the prevalence of falls among communitydwelling elderly Japanese individuals, and found that taking at least four daily prescription medications (P,0.05) was significantly associated with falls. 36 Multivariate logistic regression analysis revealed that the overall OR of falling among patients using ten or more drugs was 8.42 (95% CI 4.73-15.0) compared with patients who used 0-1 drug per day.…”
Section: Effects Of Characteristics Of Medication Use On Fall Risk Numentioning
confidence: 99%
“…Among the elderly, medication use is a crucial element among extrinsic risk factors for falls [6]. It is proven and well known that older people account for the highest proportion of medication costs, as the number of chronic diseases rapidly increases with age [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is proven and well known that older people account for the highest proportion of medication costs, as the number of chronic diseases rapidly increases with age [6,7].…”
Section: Introductionmentioning
confidence: 99%